Crosslinking-derived MnO/carbon hybrid with ultrasmall nanoparticles for increasing lithium storage capacity during cycling. (April 2016) - Kang, Danmiao; Liu, Qinglei; Si, Rui; Gu, Jiajun; Zhang, Wang; Zhang, Di
Abstract: MnO/C hybrid with ultra-small MnO nanoparticles (5.2 nm) embedded in porous carbon is fabricated and applied as the anode material for lithium ion batteries. The MnO/C hybrid electrode exhibits excellent specific capacity of 820 mAh g −1 at a current density of 100 mA g −1 and also outstanding rate performance with specific capacity of 483 mAh g −1 at a current density of 5000 mA g −1 . After cycling for 1000 times at 1000 mA g −1, the specific capacity increases to 1625 mAh g −1 . The TEM photos show that the particles are broken into 2 nm particles after cycling. We also apply XAFS to detect the final state of the Mn in the hybrid electrodes and find that smaller MnO particles are oxidized to a mixture of Mn2 O3 and MnO2 .